Ownership thinking [ how to end entitlement and create a culture of accountability, purpose, and profit - Hams, Brad (McGraw-Hill, 2012)
A tool kit for eliminating the damaging "entitlement culture" that dominates today's workplace--and motivating employees to take ownership of their work and perform as stakeholders in the business